Sylvian Fissure and Parietal Anatomy in Children with Autism Spectrum Disorder - Tracey A. Knaus; Helen Tager-Flusberg; Anne L. Foundas (Behavioural Neurology)
Autism spectrum disorder (ASD) is characterized by deficits in social functioning and language and communication, with restricted interests or stereotyped behaviors. Anatomical differences have been found in the parietal cortex in children with ASD, but parietal subregions and associations between Sylvian fissure (SF) and parietal anatomy have not been explored. In this study, SF length and anterior and posterior parietal volumes were measured on MRI in 30 right-handed boys with ASD and 30 right-handed typically developing boys (7–14 years), matched on age and non-verbal IQ. There was leftward SF and anterior parietal asymmetry, and rightward posterior parietal asymmetry, across groups. There were associations between SF and parietal asymmetries, with slight group differences. Typical SF asymmetry was associated with typical anterior and posterior parietal asymmetry, in both groups. In the atypical SF asymmetry group, controls had atypical parietal asymmetry, whereas in ASD there were more equal numbers of individuals with typical as atypical anterior parietal asymmetry. We did not find significant anatomical-behavioral associations. Our findings of more individuals in the ASD group having a dissociation between cortical asymmetries warrants further investigation of these subgroups and emphasizes the importance of investigating anatomical relationships in addition to group differences in individual regions.